Reviews of environmental contamination and toxicology. Volume 240 - Voogt, Pim de (Springer, 2017)
Reviews of Environmental Contamination and Toxicology attempts to provide concise, critical reviews of timely advances, philosophy and significant areas of accomplished or needed endeavor in the total field of xenobiotics, in any segment of the environment, as well as toxicological implications.- Resumé vydavatel
Keywords: ekotoxikologie; kvalita vody; znečištění vod; monitorování životního prostředí; environmentální chemie; environmental toxicology; water quality; water pollution; environmental monitoring; environmental chemistry; elektronické knihy; sborníky; electronic books; papers of several authors